(3efXheI aj GdaVjdIs - (3YHO GdeMehO Hf fhQ GdOGFe NdjaIs ((3eMeO WjH GdCSeGA s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JhMjOg jfLhG Hg jhe GdbVG YHjOg s
(3BNQgG (B:s
(3Ch bGd eMehO dOi GdJeGe jG QH Udi Ydi GdNJGe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdShOGf (B_ (3jhfSch s
Keywords: (3GdJhMjO hGdedd hGdfMds